2018
DOI: 10.1186/s12913-018-3706-5
|View full text |Cite
|
Sign up to set email alerts
|

“Sometimes it is difficult for us to stand up and change this”: an analysis of power within priority-setting for health following devolution in Kenya

Abstract: BackgroundPractices of power lie at the heart of policy processes. In both devolution and priority-setting, actors seek to exert power through influence and control over material, human, intellectual and financial resources. Priority-setting arises as a consequence of the needs and demand exceeding the resources available, requiring some means of choosing between competing demands. This paper examines the use of power within priority-setting processes for healthcare resources at sub-national level, following d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…Such observations in the Philippines are not unique. Other studies have likewise reported on how, for example, tribal affiliations rather than qualifications influenced the hiring of staff by local governments in Kenya [41], or how decisions for local health services in Indonesia and Kenya were made based on their appeal to the electorate [42,43], or how political interference in health planning in Tanzania led to a complex relationship between the local politician and the local government technocrat [44].…”
Section: Discussionmentioning
confidence: 99%
“…Such observations in the Philippines are not unique. Other studies have likewise reported on how, for example, tribal affiliations rather than qualifications influenced the hiring of staff by local governments in Kenya [41], or how decisions for local health services in Indonesia and Kenya were made based on their appeal to the electorate [42,43], or how political interference in health planning in Tanzania led to a complex relationship between the local politician and the local government technocrat [44].…”
Section: Discussionmentioning
confidence: 99%
“…Because of these limitations in community health in many countries, even where evidence exists, it is perceived as irrelevant and decision-makers are not encouraged to use it. The third limitation is capacity for evidence selection, understanding and use in community health decision-makers; this is a finding from consistent with wider studies in LMIC health systems ( Stansfield et al , 2006 ; Wickremasinghe et al , 2016 ; McCollum et al , 2018b , c ; Vanyoro et al , 2019 ). Comprehensive planning for community health programmes would involve decision-makers assessing an extensive set of routine data from health information systems that include: census, vital events, monitoring, public health surveillance, resource tracking, facility-based service statistics and household surveys ( Stansfield et al , 2006 ).…”
Section: Discussionmentioning
confidence: 82%
“…Overall, this builds on the work of McCollum et al from the Kenyan context showing that a lack of high-quality, relevant evidence and limited capacity to use it, compounded by external influences, allows power and politics to trump evidence use in many community health programming decisions ( McCollum et al , 2018c ). We add the generalizability of these findings beyond priority setting and into non-devolved systems.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This enabled us to gain an in-depth understanding of the gaps in providing CPAP in newborn care and to identify solutions in the context of a devolved, but resource-constrained public healthcare system, with different governance structures. [22][23][24][25][26] The inclusion of private/mission hospitals also enabled us to gain diverse perspectives on CPAP use in Kenya in the context of differing levels of resources.…”
Section: Methodsmentioning
confidence: 99%